2022
DOI: 10.34069/ai/2022.54.06.28
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of artificial intelligence in education in the arab world

Abstract: In recent years, many technological innovations that have contributed to the success of the educational process, and artificial intelligence is one of these recent innovations. Artificial intelligence has become one of the technological tools used in education and demonstrated a successful emergency strategy during the pandemic of Covid-19. This study aimed to focus on the role artificial intelligence played in education in Arabs world during the last five years. This study conducted a comprehensive survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This approach provides a deeper and more refined grasp of Morocco's complex cultural and linguistic landscape, going beyond traditional approaches to embrace a future in which every student's unique background is acknowledged and valued during the learning process. By examining behavioral data and preferences, ML algorithms may modify educational content to correspond with each learner's cultural surroundings [62]. LLMs can offer vital support in multilingual teaching, which is especially relevant in a country where various languages are spoken [63].…”
Section: Cultural and Linguistic Inclusivity In Moroccan Education: E...mentioning
confidence: 99%
“…This approach provides a deeper and more refined grasp of Morocco's complex cultural and linguistic landscape, going beyond traditional approaches to embrace a future in which every student's unique background is acknowledged and valued during the learning process. By examining behavioral data and preferences, ML algorithms may modify educational content to correspond with each learner's cultural surroundings [62]. LLMs can offer vital support in multilingual teaching, which is especially relevant in a country where various languages are spoken [63].…”
Section: Cultural and Linguistic Inclusivity In Moroccan Education: E...mentioning
confidence: 99%
“…[16] In the Arab world, Alzahrani (2022) concluded that many scholars considered AI a new technology that is helpful in the learning process. [17] Current work studies emphasized the remarkable contribution of the Bb-LMS platform. Hence, the opportunities of the Blackboard learning management system can elevate the standards of nursing education by responding effectively to the changing technological forces that affect the healthcare system.…”
Section: Prospects Of Bb-lms In the Nursing Educationmentioning
confidence: 99%
“…Artificial Intelligence (AI) is a branch of computer science that attempts to mimic the human mind's ability to learn and make decisions (Haneya et al, 2021). Artificial intelligence systems aim to build systems that are intelligent and capable of learning possessing the ability to create specialized knowledge and discover new phenomena (Alzahrani, 2022). It is one of the newest innovative technologies that have changed teaching and learning processes and replaced large portions of the decision-making process In addition, there is a high overall cost associated with creating a machine that can simulate human intelligence and frequently update it; therefore, not every country can afford it (Sourani, 2019& Mahmoud, 2020.…”
Section: Faculties Of Educationmentioning
confidence: 99%